Big win: Improving grasslands - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
The total number of livestock worldwide is estimated at 17 billion. Around two thirds - 5 billion hectares - of the world’s total agricultural area is used to feed these animals, including 3.4 billion hectares of grazing land. Much of this land has been severely degraded by overgrazing and unsustainable production.